Vooraan v.l.n.r: Hoogendoorn-Herfkens, Grotenhuis, Van den Heuvel, Reuvekamp, Heyne den Bak, van Thijn. 2e rij v.l.n.r.: Boogaard, Ter Beek, Schröder, Koopman, Toussaint. Daarachter v.l.n.r : ?, Van der Gaast, Van der Hek, Peper, Van der Doef, Rottenberg, Van Dijk, Gortzak, Buurmeijer - Morelis, Nick (1977)
Vooraan v.l.n.r: Hoogendoorn-Herfkens, Grotenhuis, Van den Heuvel, Reuvekamp, Heyne den Bak, van Thijn. 2e rij v.l.n.r.: Boogaard, Ter Beek, Schröder, Koopman, Toussaint. Daarachter v.l.n.r : ?, Van der Gaast, Van der Hek, Peper, Van der Doef, Rottenberg, Van Dijk, Gortzak, Buurmeijer.